The Relationship Between Learning Motivation And Pediatric Learning Outcomes at SMA Negeri 20 West Seram - Mesinay, Chrisna L.; Umnehopa, W.; Rumahlewang, E. (Peneliti.net, 2024)
Motivation plays a very important role in learning outcomes in physical education, sports and health of students. Because the motivation provided must arouse students' enthusiasm for learning, there are two types of motivation, namely intrinsic and extrinsic motivation. Learning outcomes are the most important part of learning. Student learning outcomes are essentially changes in behavior as a result of learning in a broader sense including the cognitive, affective and psychomotor fields. This research aims to determine whether or not there is a relationship between Learning Motivation and Health and Recreation Physical Education Learning Outcomes in Class XI SMA students. Negeri 20 Seram West. This research uses a quantitative research approach, with a correlation research design. The Pearson correlation value between the variables (Learning Motivation and Learning Results) is 0.438 (r calculated) which is greater than 0.381 (r table) with a total (N) of 25. This shows that the data on the learning motivation variable (X) and the learning outcome variable ( Y) correlates with a significance value (2-tailed) of 0.28, which means there is a positive relationship between learning motivation and student learning outcomes at SMA Negeri 20 Seram Barat. Thus, the lack of motivation to learn in students has shown its real effectiveness, in the sense of the word lack of motivation in students has a big influence on the learning outcomes of students at SMA Negeri 20 West Seram.